ANALYSIS OF THE 0,4 kV SMART GRID ISLANDING PREVENTION METHOD - V. F. Sivokobylenko; A. P. Nikiforov; V. V. Burlaka; S. K. Podnebennaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The article analyzes the methods affecting autonomous operation regimes of the powergrid sections with distributed electric-power sources (distributed generation) whose connection to the electric-power grid is realized by means of special distributed generation inverters. The authors evidentiate the reasons for which autonomous operation is undesirable; examine consequences of the autonomous asynchronous operation of the grid-sections during islanding. These problems are innate for the modern Smart Grid networks. Islanding detection methods include passive and active ones. The passive methods rely only on observation of the voltage and/or frequency at the point of common coupling (PCC) disconnecting the inverter if the  measured  values  are  outside  the  specified  limits.  Despite  their  simplicity,  passive methods cannot assure reliable islanding detection, especially in the cases when distributed generation power equals the power of loads in the potential grid-island. The active methods assume the inverter affecting the grid with the view of detecting deviation from the standard regime parameters in the PCC. Although these methods have much better islanding detection ability, their utilization reduces the power-grid operation quality.The paper holds that the grid-sections autonomous regime detection without virtually no failure-to-detect zone is only possible with employment of effective anti-islanding schemes such as connecting capacitor batteries to the disconnected power-grid sector. If appropriate providing enhanced survivability and continuity of power supply, the authors recommend providing islanding detection lock option in the inverters of the distributed generation sources.